2017
DOI: 10.1177/1758834016687482
|View full text |Cite
|
Sign up to set email alerts
|

Combination of metformin and curcumin targets breast cancer in mice by angiogenesis inhibition, immune system modulation and induction of p53 independent apoptosis

Abstract: Background:The effects of metformin (MET) and curcumin (CUR) single treatments have been tested against breast cancer; however, their combination has not been explored. Here, we evaluated the antitumor activity of MET and CUR combination against breast cancer in mice.Materials and methods:The antiproliferative activity of single and combined treatments against breast cancer cell lines was determined. Vascular endothelial growth factor (VEGF) and Trp53 expression was examined in EMT6/P cells. In vivo studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 75 publications
1
43
0
4
Order By: Relevance
“…Together, MTFN and CURC appear to have converging points to synergize in halting tumorigenicity as a whole but also each can affect specific molecules or pathways within cancer cells. Co-treatment with MTFN and CURC indeed inhibits cancer growth, metastasis, angiogenesis in-vitro and in vivo [33], modulates immune system, and induces apoptosis independent from p53 in BC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Together, MTFN and CURC appear to have converging points to synergize in halting tumorigenicity as a whole but also each can affect specific molecules or pathways within cancer cells. Co-treatment with MTFN and CURC indeed inhibits cancer growth, metastasis, angiogenesis in-vitro and in vivo [33], modulates immune system, and induces apoptosis independent from p53 in BC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Dosage range between 50 ug/kg to 200mg/kg were effectively inhibit breast cancer growth as reported in previous studies on various animal model species [11], [21], [22]. However, curcumin dosage of 50mg/kg was used to Balb/c mice induced EMT6 breast cancer tumor size [12]. Therefore this study is used as reference.…”
Section: Selection Of Curcumin Dosementioning
confidence: 91%
“…The tumor growth in female CD1 nude mice suppressed by the combination treatment of curcumin (200mg/kg/day) and epigallocethun gallate (25mg/kg/day) for 10 weeks [11]. Further, study reported that combination of curcumin (50mg/kg) and metformin (80mg/kg) in 14 days showed the highest significant reduction in the tumour size [12]. While the combination of taxol with curcumin in the BT-474 xenograft model had an antitumour effect comparable with taxol and herceptin treatment [10].…”
Section: Introductionmentioning
confidence: 97%
“…When utilized in HNSCC, the anticarcinogenic properties of curcumin include induction of apoptosis, cell cycle arrest, radiosensitivity, and chemotherapy sensitization . Dual treatment with both curcumin and metformin has been reported in hepatocellular carcinoma, pancreatic cancer cells, and breast cancer with the results suggesting synergistic effects. Combined treatment with metformin and curcumin is also thought to enhance chemoprevention properties, in vitro and in vivo, in oral cancer …”
Section: Introductionmentioning
confidence: 99%